Parallel implementation of genomic sequences classification using modified Gabor wavelet transform on multicore systems - Gunawan, Teddy Surya; Ambikairajah, Eliathamby (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/